Revitalisasi Usaha Kesehatan Sekolah (UKS) Melalui Edukasi Sekolah Sehat di Sekolah Dasar Negeri 01 Kebalen Bekasi - Fara Diba Catur Putri; Fenty Nur Aisyah; Adek Putri Puspitasari; Febriani Ayu Ardana (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The pandemic that has been going on for more than two years has changed many things, including the activity patterns of students. Not only that, this condition is exacerbated by the poor eating habits of students in various schools. problems related to the nutritional condition of students. The nutritional condition of SD Negeri Kebalen 01 Bekasi students is closely related to the consumption patterns adopted by students in their daily life in the school environment. Students seem to enjoy consuming snacks and drinks with high levels of sugar, flavourings, and salt. The next problem that is seen in students is the drastic reduction in physical activity carried out by students outside the school environment. This is due to the habits of students who spend more time playing smartphones and the various game applications contained in them. The purpose of carrying out this community service activity is to instill an understanding of the importance of healthy living behavior through strengthening the 'Healthy Schools' campaign. The method used in this activity is counseling. The results of the activity show that the activity has been running without significant obstacles where the participants' involvement in the whole extension process shows high enthusiasm and interest. The existence of interest, attention and high motivation makes the potential of participants in understanding the material presented wide open implementation.